Identification of telomere maintenance-driven molecular subtypes in hepatocellular carcinoma: implications for prognosis and targeted therapy via KPNA2 - Zhicheng Xu; Hanyu Wang; Haixia Tian; Weijing Wang; Dong Hua (Discover Oncology)
Abstract Background Telomere maintenance (TM) plays a pivotal role in regulating the pathogenesis of hepatocellular carcinoma (HCC) and is crucial for defining the clinical characteristics of patients. Despite previous publications highlighting the correlation between individual TM-related genes and HCC, comprehensive exploration and systematic analysis of these genes are still lacking. Methods Through the analysis of transcriptome data, we identified two distinct clusters (termed telomere maintenance-associated clusters, or TCs) that exhibited marked heterogeneity in clinical traits and the tumor microenvironment. Following this, we conducted an exhaustive screening process to select 15 prognostic genes related to telomere maintenance and developed corresponding TM scores for these genes. Additionally, we rigorously validated the expression and oncogenic functions of karyopherin subunit alpha 2 (KPNA2) in both HCC tissues and cell lines. Results TC1 demonstrated a significant correlation with cellular differentiation and the fatty acid metabolism pathway, while also predicting a low tumor mutation burden (TMB) alongside favorable prognostic outcomes. In contrast, TC2 was intricately linked to TM, cell cycle regulation, and DNA repair. When examining the relationship between TMB and overall survival rates. Notably, substantial heterogeneity was observed among the various TCs. Furthermore, KPNA2 exhibited upregulation and has the potential to enhance HCC proliferation and migration. Conclusion In summary, through the integration of bioinformatics and functional experimentation, we have delineated two distinct molecular classifications predicated on their association with TM-related genes in HCC. This groundbreaking discovery holds the potential to introduce innovative concepts and novel biomarkers into clinical practice.